2011
DOI: 10.1371/journal.pgen.1002370
|View full text |Cite
|
Sign up to set email alerts
|

PcG Complexes Set the Stage for Epigenetic Inheritance of Gene Silencing in Early S Phase before Replication

Abstract: Polycomb group (PcG) proteins are part of a conserved cell memory system that conveys epigenetic inheritance of silenced transcriptional states through cell division. Despite the considerable amount of information about PcG mechanisms controlling gene silencing, how PcG proteins maintain repressive chromatin during epigenome duplication is still unclear. Here we identified a specific time window, the early S phase, in which PcG proteins are recruited at BX-C PRE target sites in concomitance with H3K27me3 repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 55 publications
11
39
0
1
Order By: Relevance
“…We suspect that binding with Sce might stabilize Pc, which is crucial for PRC1 assembly. It is interesting to note that the level of Pc changes rapidly in the cell cycle (Lanzuolo et al, 2011;Follmer et al, 2012). The oscillation of Pc protein during the cell cycle is thought to be important for establishment and maintenance of cellular epigenetic memory (Follmer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that binding with Sce might stabilize Pc, which is crucial for PRC1 assembly. It is interesting to note that the level of Pc changes rapidly in the cell cycle (Lanzuolo et al, 2011;Follmer et al, 2012). The oscillation of Pc protein during the cell cycle is thought to be important for establishment and maintenance of cellular epigenetic memory (Follmer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Pc protein is known to fluctuate in cell cycle both in vitro (Lanzuolo et al, 2011;Follmer et al, 2012) and in vivo (Buchenau et al, 1998;Steffen et al, 2013), but how this process is regulated is largely unknown. We found that the abundance of Pc protein was reduced in cultured fly S2 cells treated with colchicine to induce mitotic arrest (Rogers et al, 2009;Follmer et al, 2012).…”
Section: Physiological Relevance Of Inverse Relationship Between Stx mentioning
confidence: 99%
“…This mechanism keeps the level of H3K27me3 above a certain threshold and thus precludes the unauthorized gene activation. 22 These studies imply that H3K27 methylation pattern is rather maintained via local overmethylation of parental histones followed by their dilution, than by rapid "on-therun" placement of methylation marks into the nascent chromatin.…”
mentioning
confidence: 98%
“…As suggested, this leads to the accumulation of histones bearing this modification that are later being used as a supply during the replication of the repressed regions at the end of the Sphase. 22 According to our model, SUUR protein may function as one of the factors required for this process.…”
mentioning
confidence: 99%
“…Several models have been proposed to describe the dynamic behavior of Pc complex binding (Beisel and Paro, 2011;Bracken and Helin, 2009;Hansen et al, 2008;Lanzuolo et al, 2011).…”
Section: Silencing Mechanisms Of Polycomb Complexesmentioning
confidence: 99%